Co-cultured Lepista sordida and Pholiota nameko polysaccharide-iron(iii) chelates exhibit good antioxidant activity. Issue 46 (22nd July 2020) - Yu, Shuping; Jiang, Jikang; Li, Wenxiang
Abstract : In the present study, the structural characteristics and antioxidant activities of polysaccharide from the co-cultured Lepista sordida and Pholiota nameko and its polysaccharide-iron(iii ) chelates were determined. Abstract : In the present study, the structural characteristics and antioxidant activities of polysaccharide from the co-cultured Lepista sordida and Pholiota nameko and its polysaccharide-iron(iii ) chelates were determined. Two polysaccharide fractions named CP-1 and CP-3 were isolated previously from polysaccharide of the fermentation liquid of the co-cultured Lepista sordida and Pholiota nameko . And their chemical structures were measured by FT-IR infrared spectroscopy, TG analysis, X-ray diffraction and 1 H NMR spectroscopy. The results suggested that polysaccharides were chelated with iron(iii ) by –OH and –COOH groups, forming a stable structure of β-FeOOH and improving crystallinity. Furthermore, the antioxidant activities of polysaccharide-iron(iii ) chelates exhibited stronger hydroxyl radical and superoxide radical scavenging activity than the polysaccharides. Therefore, the polysaccharide-iron(iii ) chelates could be used as a potential iron supplement.